Revolutionizing Library Services: The Impact of Artificial Intelligence on Cataloguing and Access to Information in Nigeria Academic Libraries - Ogungbenro, Olabisi Docars; Esse, Ugwunwa C.; Olowoporoku, Isaac; Christopher, Abraham (Journal of library metadata, 2025)
This research investigates the transformative function of artificial intelligence (AI) in improving cataloguing and access to information in Nigerian university libraries. The use of AI technology in library operations has resulted in considerable breakthroughs, including meeting the changing needs of digitally savvy users and optimizing the management of massive information resources. Artificial intelligence has the potential to transform cataloguing operations, improve information access, and position academic libraries as key knowledge hubs. Nigerian academic libraries may greatly improve their service delivery by adopting AI technologies that support research, teaching, and learning in the digital age. By analyzing the historical backdrop of cataloguing, the study emphasizes the limitations of traditional methods as well as AI-driven solutions. This paper investigates key AI tools like machine learning, natural language processing, and robotic process automation, providing examples of their use in automating metadata extraction, enhancing search capabilities, and personalized user experiences. The study outlines significant AI implementation issues, such as data consistency, ethical considerations, and technical training requirements, and makes solutions for overcoming these obstacles. Recommendations such as Continuous training, collaboration, user engagement, ethical considerations, and infrastructure investment were made in other to increase the influence of AI on library services.